Pengaruh Penambahan Kompos Campuran Kiapu dan Jerami Padi Berulang Terhadap Pertumbuhan dan Hasil Tanaman Padi Sawah (Oryza sativa L.) - Mega Meylinda; Anis Sholihah; Siti Muslikah (AGRONISMA, 2019)
ABSTRACTThis study aims to determine the effect of adding kiapu mixture and recurrent rice straw to the growth and yield of second period wetland rice. The design used was RAK, the treatment (R1 + = 100% kiapu; R2 + = 75% kiapu + 25% rice straw; R3 + = 50% kiapu + 50% rice straw; R4 + = 25% kiapu + 75% rice straw ; R5 + = 100% rice straw) plus NPK treatment and control. The results showed that the Kiapu mixture compost R1 + had an average variable growth of 96.58 cm, the number of leaves was 236.17 pot -1, the number of tillers was 55.83 pot-1, leaf area was 9646 , 07 cm2, total root length of 606.28 cm and the highest yield of grain weight per hectare of 9.67 tons ha-1 was better than all treatments.Key words: Kiapu, rice straw, lowland rice